Green criminology and (constructions of) environmental crime and harm: a review essay - Mol, Hanneke (2016)
Brisman and South: Green Cultural Criminology: Constructions of Environmental Harm, Consumerism, and Resistance to Ecocide. Routledge, Oxford and New York, 2014, 162 pp Brisman, South, and White: Environmental Crime and Social Conflict: Contemporary and emerging issues. Ashgate, Farnham and Burlington, 2015, 328 p